Mindful Consumption in Islamic Economics: A Conceptual Analysis within the Framework of Sustainability - Anggraini, Misi (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
This research examined the concept of mindful consumption in Islamic economics to measure the balance between needs, ethics, and sustainability. A qualitative juridical-normative method was used through literature review, Islamic law analysis, and case studies of consumer behavior. The research results showed that mindful consumption encouraged moderation by fulfilling real needs while integrating ethical considerations and environmental preservation. This approach created consumption patterns that were not only material but also considered moral, social, and spiritual dimensions. Conscious consumption affirmed social-spiritual values, strengthened the relationship with God, and encouraged social responsibility through simple, halal, and responsible living. Mindful consumption aligned with maqashid shariah, which included social justice and environmental preservation, avoiding wastefulness (israf) and exploitation. The implementation of this concept contributed to a just, harmonious, and sustainable society, as well as supported the Sustainable Development Goals (SDGs) and overall community welfare.